A genome‐wide RNAi screen reveals essential therapeutic targets of breast cancer stem cells. Issue 10 (2nd September 2019) - Arfaoui, Abir; Rioualen, Claire; Azzoni, Violette; Pinna, Guillaume; Finetti, Pascal; Wicinski, Julien; Josselin, Emmanuelle; Macario, Manon; Castellano, Rémy; Léonard‐Stumpf, Candi; Bal, Anthony; Gros, Abigaelle; et al.
Abstract: Therapeutic resistance is a major clinical challenge in oncology. Evidence identifies cancer stem cells (CSCs) as a driver of tumor evolution. Accordingly, the key stemness property unique to CSCs may represent a reservoir of therapeutic target to improve cancer treatment. Here, we carried out a genome‐wide RNA interference screen to identify genes that regulate breast CSCs‐fate (bCSC). Using an interactome/regulome analysis, we integrated screen results in a functional mapping of the CSC‐related processes. This network analysis uncovered potential therapeutic targets controlling bCSC‐fate. We tested a panel of 15 compounds targeting these regulators. We showed that mifepristone, salinomycin, and JQ1 represent the best anti‐bCSC activity. A combination assay revealed a synergistic interaction of salinomycin/JQ1 association to deplete the bCSC population. Treatment of primary breast cancer xenografts with this combination reduced the tumor‐initiating cell population and limited metastatic development. The clinical relevance of our findings was reinforced by an association between the expression of the bCSC‐related networks and patient prognosis. Targeting bCSCs with salinomycin/JQ1 combination provides the basis for a new therapeutic approach in the treatment of breast cancer. Synopsis: The development of cancer stem cell‐targeting therapies is of major interest and requires insight into the underlying mechanisms. In this study, a genome‐wide RNAi screen was established, and revealed essential therapeutic targets of breast cancer stem cells (bCSC). bCSC‐related processes were identified by functional mapping integrating RNAi screens. bCSC‐related processes represented a reservoir of therapeutic target. Salinomycin synergized with JQ1 treatment to reduce the bCSC population and limit tumor progression. bCSC‐related processes were associated with poor prognosis in breast cancer patients. Abstract : The development of cancer stem cell‐targeting therapies is of major interest and requires insight into the underlying mechanisms. In this study, a genome‐wide RNAi screen was established, and revealed essential therapeutic targets of breast cancer stem cells (bCSC).